2016
DOI: 10.1016/j.virol.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Hemopoietic cell kinase (Hck) and p21-activated kinase 2 (PAK2) are involved in the down-regulation of CD1a lipid antigen presentation by HIV-1 Nef in dendritic cells

Abstract: Dendritic cells (DCs) play a major role in in vivo pathogenesis of HIV-1 infection. Therefore, DCs may provide a promising strategy to control and eventually overcome the fatal infection. Especially, immature DCs express all CD1s, the non-MHC lipid antigen -presenting molecules, and HIV-1 Nef down-regulates CD1 expression besides MHC. Moreover, CD1d-restricted CD4(+) NKT cells are infected by HIV-1, reducing the number of these cells in HIV-1-infected individuals. To understand the exact role of DCs and CD1-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Short interfering RNAs (siRNAs) targeting human CD1b (ON-TARGET plus siRNA, identifier [ID]: J-01499-05, 06, 07, and 08), targeting human CD1d (ON-TARGET plus siRNA ID: J-019429-05, 06, 07, and 08), human GAPDH (ID: D-001830-10-05), and negative control siRNA (IDs: D-001810-10-20 and D-001810-02-05) were obtained from Dharmacon (Horizon Discovery, Cambridge, U.K.), and siRNA electroporation of moDCs were performed as described previously (23). Briefly, moDCs were pulsed with the siRNAs (final 500 mM) at 250 V and 950 mF using Gene Pulser II apparatus (Bio-Rad Laboratories, Hercules, CA).…”
Section: Short Interfering Rna Transfectionmentioning
confidence: 99%
“…Short interfering RNAs (siRNAs) targeting human CD1b (ON-TARGET plus siRNA, identifier [ID]: J-01499-05, 06, 07, and 08), targeting human CD1d (ON-TARGET plus siRNA ID: J-019429-05, 06, 07, and 08), human GAPDH (ID: D-001830-10-05), and negative control siRNA (IDs: D-001810-10-20 and D-001810-02-05) were obtained from Dharmacon (Horizon Discovery, Cambridge, U.K.), and siRNA electroporation of moDCs were performed as described previously (23). Briefly, moDCs were pulsed with the siRNAs (final 500 mM) at 250 V and 950 mF using Gene Pulser II apparatus (Bio-Rad Laboratories, Hercules, CA).…”
Section: Short Interfering Rna Transfectionmentioning
confidence: 99%
“…55 This effect may be mediated by specific HIV proteins, where Nef together with Vpu affects CD1d, 56 and Nef alone has been shown to affect CD1a antigen presentation in DCs. 57 In addition to HIV's effect on antigen presentation, it was recently reported that Mtb uses host proteins (specifically kinesin-2) to limit antigen presentation, by reducing the accumulation and availability of bacterial antigens in DCs. 58 Our observation suggests that reduction in Mtb antigen processing and further presentation by the DCs could be an immune evasion mechanism used by HIV that as a consequence further exacerbates Mtb pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism has not yet been described. In addition, HIV-1 negative factor (Nef) downregulates CD1a after infection of immature DCs with HIV-1 and impairs stimulation of CD1a-restricted T cells ( 240 , 241 ). In order to modulate host membrane trafficking pathways HIV-1 Nef has to interact with various host proteins through distinct motifs ( 242 ).…”
Section: Viral Evasion Of Cd1-restricted T Cellsmentioning
confidence: 99%
“…In order to modulate host membrane trafficking pathways HIV-1 Nef has to interact with various host proteins through distinct motifs ( 242 ). Nef-mediated CD1a downregulation might require the interaction of Nef with hematopoietic cell kinase and p21-activated kinase 2, which are both expressed in immature DCs ( 241 ). Collectively, these findings support the idea that group 1 CD1 molecules contribute to lipid-driven antiviral immune responses.…”
Section: Viral Evasion Of Cd1-restricted T Cellsmentioning
confidence: 99%